Total and Available Fluoride Content in Toothpastes Sold in Dar es Salaam, Tanzania - Ndoile, Monica Mbaraka (Tanzania Journal of Science, 2020)
A total of eleven (11) different toothpaste brands (imported and manufactured in Tanzania) sold in Dar es Salaam were evaluated for Total Fluoride (TF) and Total Soluble Fluoride (TSF) concentrations. To protect the subject’s identity, the samples were coded. Four selected toothpastes were analyzed for potentially bioavailable fluoride by examining the relationship between TSF in tooth brushing residues and in that of the toothpaste. The results indicated that measured TF of the toothpaste samples coded as TPSA, TPSC and TPSH were consistent to the one declared by the manufacturers. On the other hand, samples coded as TPSB, TPSD, TPSE, TPSF, TPSG, TPSI, TPSJ and TPSK showed discrepancies between TF declared by the manufacturers and the measured amounts. Generally, measured TSF in majority of the tested toothpastes were above the minimum required amount for dental caries prevention (≥1000 ppm). Toothpastes with amounts below minimum were, TPSF (TF = 310 ppm and TSF = 305 ppm); TPSG (TF = 350 ppm and TSF = 340 ppm); TPSI (TF = 20 ppm and TSF = 17 ppm). Significant correlations were observed between TSF in toothpastes and in that of brushing residues (r = 0.850; p = 0.0001). These findings indicate that TSF concentration that is chemically available in toothpastes could be used to estimate how much fluoride would be bioavailable during brushing. On the other hand, the necessity for the development of strict regulatory measures on amounts of fluoride concentrations in toothpastes sold in Dar es Salaam is recommended for effective caries control.